Impact of Entrepreneurial Leadership on Organization Demand for Innovation: Moderating Role of Employees' Innovative Self-Efficacy - Mokhber, Mozhdeh; Tan, Gi G.; Vakilbashi, Amin; Mohd Zamil, Nor Aiza; Basiruddin, Rohaida (International Review of Management and Marketing, 2016)
The main purpose of this paper is to examine the influence of entrepreneurial leadership and employees' self-efficacy towards organization demand for innovation. Introduction to alternative pathways of thinking and actions in an organization is typically tie-up with innovation nowadays. In this regard, the degrees of organizations willingness to engage and perceive advantage from new products or services, or products or services that embody new technology are being focused. Since leadership has been identified as a key determinant of organization innovation, a conceptual framework is proposed to explore the impact of entrepreneurial leadership on organization demand for innovation. Apart from the leadership behaviors, followers' characteristic and their own confidence level or perceived self-efficacy are also studied to capture the effect of innovative work behavior. Hence, this study aims to determine the moderating role of employees' innovative self-efficacy on the relationship between entrepreneurial leadership and organization demand for innovation. A sample from Malaysia Top 100 companies is participated and the hypotheses are evaluated using Partial Least Squares (PLS) analysis. This research makes a significant contribution by providing empirical evidence that support entrepreneurial leaders and the organizations to generate more opportunities and enact them in ways that increase the firm's receptivity towards innovation. Keywords: Entrepreneurial Leadership, Receptivity of innovation, Organizational Innovation Confidence, Innovative Self-Efficacy, PLS-SEM. JEL Classification: L22